Cultivating Learner-Centered Techniques in the Classrooms for Quality Learning and Teaching - Pandey, Shiv Ram (Journal of Innovation in Teaching and Instructional Media, 2025)
This review article entitled Cultivating Learner-Centered Techniques in the Classroom for Quality Learning and Teaching aims to explore ideas and insights on learner-centered techniques in the classrooms. It examines the learner centered techniques, methods and their needs in teaching. It discusses the concept of learner centered methods, the various types of learners centered methods, the differences between teacher centered methods and the learner centered methods. It also addresses characteristics of learner centered method, the merits of learner centered methods to students and the teacher. Techniques such as group work, problem-based learning, role play, simulation, pair work, discussion, interaction and project- based learning play a vital role to make teaching learning process meaningful and successful. This article uncovered that teacher faced challenges while implementing learner-centered techniques in their classrooms, for example, limitation of time, a large number of students, and inadequate resource materials. The study concludes that the learner centered method should be considered as it is the ideal method for teaching soft skills needed to explore the environment, work well with others, perform well and achieve goals. It suggests that the nature of curriculum need to move from traditional to modern and progressive to allow full implementation of the learner centered techniques and methods. Teachers should be exposed to modern trends in the teaching profession.